Credit Risk, Liquidity, and Capital Adequacy Levels on Profitability in Conventional Banks on the Indonesian Stock Exchange - Putu Agustini, Ni Luh; Yeni Astiti, Ni Putu; Indah Mentari, Ni Made (Admisi dan Bisnis, 2024)
Profitability is the ability of a bank to generate or obtain profits effectively and efficiently. The study aims to test the impact of Credit Risk, Liquidity, and Level of Capital Fulfillment on Profitability in Conventional General Banks listed on the Indonesian Stock Exchange. The research population is a Conventional General Bank Company that exists in Indonesia and is listed on the Indonesian Stock Exchange in 2019-2022 a total of 47 companies. The sample in this study consisted of 39 Conventional General Banks determined by purposive sampling. The total of observations in this study is 156 observations. The analytical technique used to test the hypothesis is double linear regression analysis. The results show that Credit Risk (NPL) and Capital Satisfaction Rate (CAR) have no impact on profitability. Liquidity (LDR) has a positive and significant impact on profitability. Further research can use and develop other free variables such as: solvency, financial distress, company size and others.